The Development of Ternary Nanoplexes for Efficient Small Interfering RNA Delivery - (:unkn) unknown (PHARMACEUTICAL SOC JAPAN, 2013)
Targeted posttranscriptional gene silencing by RNA interference (RNAi) has garnered considerable interest as an attractive new class of drugs for several diseases, such as cancer. Chitosan and protamine are commonly used as a vehicle to deliver and protect small interfering RNA (siRNA), but the strong interaction still remains to be modulated for efficient siRNA uptake and silencing. Therefore, in this study, ternary nanoplexes containing chitosan and protamine were designed to substantially enhance the siRNA efficiency. Binary and ternary nanoplexes were prepared at different the ratios of moles of the amine groups of cationic polymers to those of the phosphate ones of siRNA (N/P) ratios and characterized in terms of size, zeta potential, morphology and serum stability. The silencing efficiencies and cytotoxicities of prepared nanoplexes were evaluated by enzyme-linked immunosorbent assay (ELISA) (for human vascular endothelial growth factor; hVEGF) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays, respectively. The mean diameter of ternary nanoplexes ranged from 151 to 282nm, depending on the weight ratio between polymers and siRNA. The gene silencing effect after transfection with ternary nanoplexes (chitosan/siRNA/protamine 83%) was significantly higher than that with binary nanoplexes (chitosan/siRNA 71% and protamine/siRNA 74%). Ternary nanoplexes showed the highest cellular uptake ability when compared with binary nanoplexes. Ternary nanoplexes did not induce substantial cytotoxicity. Serum stability and the lack of cytotoxicity of the nanoplexes provided advantages over other gene silencing studies. These results suggest ternary nanoplexes have the potential to be an effective siRNA carrier to study the gene silencing effect.
Keywords: small interfering RNA; protamine; chitosan; ternary nanoplex; vascular endothelial growth factor; SIRNA DELIVERY; IN-VIVO; BREAST-CANCER; GENE DELIVERY; NANOPARTICLES; PROTAMINE; CHITOSAN; CARRIER; THERAPEUTICS; BARRIERS